Acclimatisation of guard cell metabolism to long‐term salinity. (18th December 2020) - Franzisky, Bastian Leander; Geilfus, Christoph‐Martin; Romo‐Pérez, Maria Luisa; Fehrle, Ines; Erban, Alexander; Kopka, Joachim; Zörb, Christian
Abstract: Stomatal movements are enabled by changes in guard cell turgor facilitated via transient accumulation of inorganic and organic ions imported from the apoplast or biosynthesized within guard cells. Under salinity, excess salt ions accumulate within plant tissues resulting in osmotic and ionic stress. To elucidate whether (a) Na + and Cl − concentrations increase in guard cells in response to long‐term NaCl exposure and how (b) guard cell metabolism acclimates to the anticipated stress, we profiled the ions and primary metabolites of leaves, the apoplast and isolated guard cells at darkness and during light, that is, closed and fully opened stomata. In contrast to leaves, the primary metabolism of guard cell preparations remained predominantly unaffected by increased salt ion concentrations. Orchestrated reductions of stomatal aperture and guard cell osmolyte synthesis were found, but unlike in leaves, no increases of stress responsive metabolites or compatible solutes occurred. Diverging regulation of guard cell metabolism might be a prerequisite to facilitate the constant adjustment of turgor that affects aperture. Moreover, the photoperiod‐dependent sucrose accumulation in the apoplast and guard cells changed to a permanently replete condition under NaCl, indicating that stress‐related photosynthate accumulation in leaves contributes to the permanent closing response of stomata under stress. Abstract : Guard cell metabolism differentially responds to altered ion composition resulting from salt stress (NaCl) compared with whole leaf tissue in Vicia faba L.